2013
DOI: 10.1177/1753425913501915
|View full text |Cite
|
Sign up to set email alerts
|

Activation of liver X receptor suppresses the production of the IL-12 family of cytokines by blocking nuclear translocation of NF-κBp50

Abstract: There is now convincing evidence that liver X receptor (LXR) is an important modulator of the inflammatory response; however, its mechanism of action remains unclear. This study aimed to examine the effect of LXR on the IL-12 family of cytokines and examined the mechanism by which LXR exerted this effect. We first demonstrated that activation of murine-derived dendritic cells (DC) with a specific agonist to LXR enhanced expression of LXR following activation with LPS, suggesting a role in inflammation. Further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…In the CNS, LXRs are widespread in growing or mature neurons and glial cells (Mandrekar-Colucci and Landreth, 2011). Recent studies showed that LXRα could disrupt NF-κB activation by a process called trans -repression and thus has an anti-inflammatory function (Zhang-Gandhi and Drew, 2007; Mandrekar-Colucci and Landreth, 2011; Cui et al, 2012; Canavan et al, 2013). Therefore, we investigated the role of miR-155-LXRα in regulating the heat stress-induced inflammatory response to elucidate the underlying mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…In the CNS, LXRs are widespread in growing or mature neurons and glial cells (Mandrekar-Colucci and Landreth, 2011). Recent studies showed that LXRα could disrupt NF-κB activation by a process called trans -repression and thus has an anti-inflammatory function (Zhang-Gandhi and Drew, 2007; Mandrekar-Colucci and Landreth, 2011; Cui et al, 2012; Canavan et al, 2013). Therefore, we investigated the role of miR-155-LXRα in regulating the heat stress-induced inflammatory response to elucidate the underlying mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest that acute LPS treatment induces important early transcription factors and coordinately down-regulates nuclear receptors, resulting in altered expression of a large number of downstream genes (Fang et al, 2004). Canavan et al (2013) first demonstrated that activation of murine-derived dendritic cells with a specific agonist to LXR enhanced expression of LXR following activation with LPS. Wang et al (2006) demonstrated that activation of LXR protects against liver injury and dysfunction in a rat model of endotoxemia, in part by exerting an anti-inflammatory effect on Kupffer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to PPARγ activation, also LXR activation has shown contradictory results regarding its effect on DCs. Next to its effect on DC differentiation [ 60 ], it has been shown to inhibit DC maturation [ 61 , 62 ] as well as sensitize DCs to inflammatory stimuli increasing DC maturation [ 63 ]. Also opposing effects of LXR activation on CCR7 dependent migration have been reported.…”
Section: Nuclear Receptors and Their Ligandsmentioning
confidence: 99%